<em>I think your answer is fine</em>
Answer:
f(x+1)=<em>fx+f</em>
<em>f(x)+f(6)=fx+6f</em>
<em />
Step-by-step explanation:
Length (2, 6) to (-4, 6) is sqrt((x2 - x1))^2 + (y2 - y1)^2) = sqrt((-4 -2)^2 + (6 - 6)^2) = sqrt((-6)^2 + 0) = 6
Length (2, 6) to (-4, 4) is sqrt((-4 - 2)^2 + (4 - 6)^2) = sqrt((-6)^2 + (-2)^2) = sqrt(36 + 4) = sqrt(40) = 2sqrt(10) units
Length (-4, 6) to (-4, 4) is sqrt((-4 - (-4))^2 + (4 - 6)^2) = sqrt(0^2 + (-2)^2) = 2
So the length of the longest side is 2sqrt(10) units
Are you asking something?? Or did you just answer your own question? EITHER WAY. Pretty chill... should give me brainliest if you’re up for it ;)
Answer:
4.2 team members per day
Step-by-step explanation:
5 + 4 + 2 + 7 + 3 = 21
21/5 = 4.2